Efficacy of copolymer scaffolds delivering human demineralised dentine matrix for bone regeneration - Munir, Arooj (J Tissue Eng, 2019)
Poly(L-lactide-co-ε-caprolactone) scaffolds were functionalised by 10 or 20 µg/mL of human demineralised dentine matrix. Release kinetics up to 21 days and their osteogenic potential on human bone marrow stromal cells after 7 and 21 days were studied. A total of 390 proteins were identified by mass spectrometry. Bone regeneration proteins showed initial burst of release. Human bone marrow stromal cells were cultured on scaffolds physisorbed with 20 µg/mL and cultured in basal medium (DDM group) or physisorbed and cultured in osteogenic medium or cultured on non-functionalised scaffolds in osteogenic medium. The human bone marrow stromal cells proliferated less in demineralised dentine matrix group and activated ERK/1/2 after both time points. Cells on DDM group showed highest expression of IL-6 and IL-8 at 7 days and expressed higher collagen type 1 alpha 2, SPP1 and bone morphogenetic protein-2 until 21 days. Extracellular protein revealed higher collagen type 1 and bone morphogenetic protein-2 at 21 days in demineralised dentine matrix group. Cells on DDM group showed signs of mineralisation. The functionalised scaffolds were able to stimulate osteogenic differentiation of human bone marrow stromal cells.